Examining the Relationship between Factors Influencing Environmental Behavior among Polluted River Communities - Wan Nor Azilawanie Tun Ismail , Aziz Amin (International Journal of Advanced Science and Technology, 2020)
Rivers are sources of life, providing water supply for the people, irrigation for agriculture, cheap and efficient transportation, rich sources of food, hydro-electric power, and water use for industries. Pollution in rivers can cause disease and affect the surrounding ecosystem. Human activities are a major cause of such water pollution. This research explores the significant factors affecting environmental behavior among polluted river communities in Terengganu. The approach of this research is the survey through questionnaire. Using cluster sampling, 373 respondents from selected area in polluted river in Terengganu were identified as sample. Data is analyzed using structural equation modeling. Environmental knowledge and media exposure to environmental message affected environmental behavior. Meanwhile, environmental values, attitudes, perceived behavioral control, self-efficacy, subjective norms and recycling facilities not affected environmental behavior. This study is expected to elevate community awareness, change the behavior and to involve them through participation in environmental rehabilitation activities and responsible for combating environmental pollution in their attempt to eradicate activities that destroy and pollute the environment. The river environment needs to be conserved in order to enable the river to perform all its natural functions and for a sustainable, healthy and an enhanced quality of life.